Black hole Attack Detection in AODV-BTR MANET - Gupta, Bhavana; Jian, Vikas; Tiwari, Rajesh (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
Security is a vital requirement in mobile ad hoc networks to provide secured communication among mobile nodes. Due to different characteristics of MANETS, it creates a number of consequential challenges to its security design. To overcome the challenges, there is a need to build a powerful security solution that achieves both broad protection and desirable network performance.Mobile Ad hoc Network (MANET) has emerged as a new leading edge of technology to provide communication wherever and whenever required. As the wired network needs established infrastructure for communication but the mobile ad hoc network does not need any infrastructure, centralized management and control. Due to movable nature of nodes in Mobilead hoc network difficult routing between nodes are not very easy task. For this purpose many reactive routing protocols have been implemented like AODV, DSR, and DSDV. In the first part of this work, we propose a new algorithm AODV-BTR to improve existing on demand routing protocol and an attempt has been made to compare the performance of proposed algorithm (AODV-BTR) with existing algorithm AODV. Ad hoc networks are susceptible to many types of attacks; due tomovable nature of nodes it is very difficult to provide security at each node. This paper introduces the black hole attack; in this type of attack mischievous node announce that he is having the shortest path to all nodes in the environment by sending fake route reply message. This paper proposes an easiest way to detect Black hole attacks using DLM technique. DML method presents the solution to detect & remove blackhole attack in reactive protocol called AODV-BTR.